Pengaruh Metode Memory Power terhadap Hasil Belajar Siswa Kelas IV Materi Perubahan Kenampakan Bumi - Kartika, Dea Novi; Wuryastuti, Sri (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Based on the results of observations made by researchers, there are still many teachers who use conventional methods such as lecture and question and answer methods in delivering a lesson in learning activities, especially in science learning. For this reason, researchers tried to apply the memory method in studying the concept of changes in the Appearance of Earth and Celestial Objects. Memory is a surefire way to improve memory by optimizing the function of the left and right hemispheres of the brain in a balanced way. The research method used in this research is the Quasi-Experimental Design Method and the type of design used is the Nonequivalent Control Group Design. The sample used was class IV B SDN Talagasari1, which consisted of 10 students in the control group and 10 students in the experimental group. The research instrument was in the form of a test, namely 10 essay questions, and a non-test in the form of an interview. The data found from the test results were then processed using SPSS Version 16 software for Windows and the following data were obtained: The average gain of the experimental group is 3 which is at a high level, while the average gain of the control group is 2 which is at the medium level. This gain test shows that the experimental group experienced a good increase compared to the control group after treatment using the memory power method. The use of the memory power method can evidently have an effect on improving student learning outcomes in the material of Changes in Earth's Landscape.